TRANSPORT COMPETITIVENESS – FACTOR OF ECONOMIC STATE SECURITY - A. D. Molokovitch; V. D. Antjushenja (Наука и техника)
The paper proposes main criteria for evaluation of economic state security in the field of transport. Methodology for determination of general index of transport service quality has been developed. It is based on single quality indices. Methodology for evaluation of transport component in the product price which permits to determine optimal variants of cargo transportation has been also developed. Normal and threshold values of the general index of transport service quality have been determined in the paper.